The backyard blacksmith traditional techniques for the modern smith - Sims, Lorelei (Gloucester, Mass. : Quarry Books, 2006)
This book shows you how blacksmithing can be easy to learn, and a rewarding hobby, with some patience and a working knowledge of metals, basic tools, and techniques.
Section 1. Getting your feet wet. Your smithy -- Gathering tools and equipment -- Iron -- Preliminary skills -- Section 2. Getting your hands dirty. Tool usage and forging techniques -- Forge welding and other assemblage techniques -- Making your own tooling -- Section 3. Getting in the groove. Projects.
Includes index.
Keywords: Blacksmithing -- Amateurs' manuals; Handbooks and manuals